Pelatihan Hidroponik dan Pengomposan di Tingkat SMA dalam Rangka Persiapan Adiwiyata: Pelatihan Hidroponik dan Pengomposan - Listin Fitrianah; Laily Noer; Ardhana Rahmayanti; Lily Oktavia; Atik Widiyanti; Elsa Rosyidah; Rina Sri Wulandari; Luqman Hakim; Waluyo Prasetyo; Medya Ayunda; Yulia Tri Rahkadima (Universitas Nahdlatul Ulama Sidoarjo, 2021)
Limited land and high land prices are obstacles experienced by the development of settlements and schools. However, school institutions have a responsibility in shaping the character of caring for the environment in students. Therefore, hydroponic and composting training was conducted at the high school level with the aim that students gain knowledge and experience in farming using hydroponic methods and composting using waste in schools. The training method carried out includes 3 stages. The first stage is preparation with teachers to conduct training with students. Furthermore, at the implementation stage, hydroponic and composting training was carried out with high school schools in Lamongan regency. The last stage is an evaluation of activities with the school. The results of the training showed that 45% of participants were interested in hydroponic training and 65% were interested in composting training, 57% of participants were motivated in the application of hydroponics and composting in their respective schools. In addition, as many as 55% have a desire to learn more about the training that has been carried out. And 60% of the participants have the desire to pursue hydroponic and composting business.